Differentially methylated gene patterns between age‐matched sarcopenic and non‐sarcopenic women. Issue 6 (11th September 2019) - He, Lingxiao; Khanal, Praval; Morse, Christopher I.; Williams, Alun; Thomis, Martine
Abstract: Background: Sarcopenia is characterized by progressive decreases in muscle mass, muscle strength, and muscle function with ageing. Although many studies have investigated the mechanisms of sarcopenia, its connection with epigenetic factors, such as DNA methylation, still remains poorly understood. The aim of this study was to explore sarcopenia‐related DNA methylation differences in blood samples between age‐matched sarcopenic and non‐sarcopenic older women. Methods: A sarcopenic group ( n = 24) was identified and selected from a set of 247 older Caucasian women (aged 65–80 years) based on cut‐off points of skeletal muscle index at 6.75 kg/m 2 and grip strength at 26 kg (the lower quintile of grip strength in the set). A non‐sarcopenic group ( n = 24) was created with a similar age distribution as that of the sarcopenic group. DNA methylation patterns of whole blood samples from both groups were analysed using Infinium MethylationEPIC BeadChip arrays. Differentially methylated cytosin–phosphate–guanine sites (dmCpGs) were identified at a P value threshold of 0.01 by comparing methylation levels between the sarcopenic and non‐sarcopenic groups at each CpG site. dmCpG‐related genes were annotated based on Homo sapiens hg19 genome build. The functions of these genes were further examined by GO and KEGG pathway enrichment analysis. Results: The global methylation level of all analysed CpG sites ( n = 788 074) showed no significant difference between the sarcopenic and non‐sarcopenic groups (0.812), while the average methylation level of dmCpGs ( n = 6258) was significantly lower in the sarcopenic group (0.004). The sarcopenic group had significantly higher methylation levels in TSS200 (the region from transcription start site to 200 nucleotides upstream of the site) and lower methylation levels in gene body and 3'UTR regions. In respect of CpG regions, CpG islands in promoters and some intragenic regions showed greater levels of methylation in the sarcopenic group. dmCpG‐related KEGG pathways were mainly associated with muscle function, actin cytoskeleton regulation, and energy metabolism. Seven genes ( HSPB1, PBX4, CNKSR3, ORMDL3, MIR10A, ZNF619, and CRADD ) were found with the same methylation direction as previous studies of blood sample methylation during ageing. Fifty‐four genes were shared with previous studies of resistance training. Conclusions: Our results improve understanding of epigenetic mechanisms of sarcopenia by identifying sarcopenia‐related DNA methylation differences in blood samples of older women. These methylation differences suggest underlying alterations of gene expression and pathway function, which can partially explain sarcopenia‐related muscular changes.